2016
DOI: 10.1016/j.chest.2015.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Phenotype and Outcomes in Pulmonary Arterial Hypertension Trials

Abstract: For the first time, using data from large randomized controlled trials, this study characterizes the different phenotype and outcomes of older patients with PAH, which includes different disease etiology, diminished functional status, and decreased response to intervention. This may have significant implications for the management of this patient population and design of future therapy trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Few studies have assessed the characteristics of patients with IPAH based on their age [10,26] or the effect of age on treatment response [10,27]. The COMPERA study used a cut-off age of 65 years [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have assessed the characteristics of patients with IPAH based on their age [10,26] or the effect of age on treatment response [10,27]. The COMPERA study used a cut-off age of 65 years [10].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, data from six large randomised controlled trials including patients with IPAH and associated PAH were presented in a meta-analysis [27]. The results indicated that older patients were more often classified into New York Heart Association FC III-IV and had shorter 6MWD, but had better hemodynamic status at baseline than younger patients.…”
Section: Discussionmentioning
confidence: 99%
“…1−7 At least in Western countries, the proportion of patients being diagnosed at a more advanced age and/or with more risk factors for left ventricular diastolic dysfunction is increasing. 8,9 Clinical outcomes are worse in such patients relative to their younger counterparts who have fewer risk factors for left ventricular diastolic dysfunction. 8,9 These observations have led to some uncertainty in how best to categorize and treat these patients based on the current clinical classification of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Clinical outcomes are worse in such patients relative to their younger counterparts who have fewer risk factors for left ventricular diastolic dysfunction. 8,9 These observations have led to some uncertainty in how best to categorize and treat these patients based on the current clinical classification of pulmonary hypertension. 10−13 Traditionally, patients with advanced age and/or risk factors for left ventricular diastolic dysfunction have largely been excluded from clinical trials with PAH medications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gender, cardiovascular risk factors and age have recently been identified as potential predictors of therapeutic response. 2 5 …”
mentioning
confidence: 99%